Reflection of three prominent religious, mythological and epic themes in mystical texts - Modir, Ahmad (2021)
Zoroaster, Jamshid and Kaykhosrow are among the personalities who have a large part of the culture and beliefs of ancient Iran. Art and literature have also provided a good platform for the widespread reflection of such wondrous themes in mystical texts. The influence of Zoroastrian teachings on the thought, culture and customs of ancient Iran is undeniable. The era of Jamshid's narration in ancient Iran and Shahnameh is highly respected for its tranquility, abundance of blessings, and abundant social services. In addition to Barkikhosrow, who is one of the virtuous and most prominent mystical figures in Avesta and Shahnameh, the epics and myths of Shahnameh have greatly influenced the mystical texts of later centuries, and mystics, referring to the myths and epics of Shahnameh, have the deepest mystical expressions. Ethical. The myth is derived from the Greek "history", meaning search, knowledge and story, and is closely linked to religious and mystical beliefs, as it contains the menu of ancient humans and the manifestation of their beliefs about the creation of the world, beings and human beings. It is worth mentioning that the main purpose of mystics in dealing with the myths and epics of Shahnameh is to express mystical themes. In this research, an attempt has been made to express three prominent religious, mythological and epic themes: Zoroaster, Jamshid, and Kaykhosrow, and how they are reflected in mystical texts, their transformation and their connections from the beginning to the stage of Islamic perfection and maturity. The method of work in this research is the use of library and written resources based on analysis and description.